2015
DOI: 10.1007/s10067-015-3080-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL8 and mRNA level of CD11b in circulating neutrophils are increased in clinically amyopathic dermatomyositis with active interstitial lung disease

Abstract: The objective of this study is to assess serum IL8 and the potential activity of circulating neutrophils on relative messenger RNA (mRNA) levels and their relationship with disease activity in clinically amyopathic dermatomyositis (CADM) associated with interstitial lung disease (ILD). We studied 18 CADM patients and compared them with 18 classic dermatomyositis (DM) patients and 18 healthy control subjects. Serum IL8 level and mRNA expressions of neutrophils (chemokine (C-X-C motif) receptor 1 (CXCR1), cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…In CSF there were many more differences in the concentrations of mediators between the aetiological groups. Specifically, higher concentrations of IL-8 were identified in both the infectious and unknown group as opposed to immune-mediated cases, which would be consistent with the key finding of the role of neutrophils in our study, given the important role of IL-8 in neutrophil activation [ 47 49 ]. In addition, greater concentrations of IL-1RA, IL-4, IL-10 and IL-1β were found in the immune-mediated group.…”
Section: Discussionsupporting
confidence: 89%
“…In CSF there were many more differences in the concentrations of mediators between the aetiological groups. Specifically, higher concentrations of IL-8 were identified in both the infectious and unknown group as opposed to immune-mediated cases, which would be consistent with the key finding of the role of neutrophils in our study, given the important role of IL-8 in neutrophil activation [ 47 49 ]. In addition, greater concentrations of IL-1RA, IL-4, IL-10 and IL-1β were found in the immune-mediated group.…”
Section: Discussionsupporting
confidence: 89%
“…Concerning interstitial lung disease (ILD), Gono et al [48] and Yang et al [49] found that IL-18 was higher in DM-associated ILD (DM-ILD) compared to DM without ILD but no difference was found between RP-ILD compared to non-RP-ILD [23, 51]. Zou et al [52] confirmed these results in CADM neutrophils: they found an increase of IL-18 mRNA in CADM patients compared to classical DM (cDM) and HD.…”
Section: Resultsmentioning
confidence: 99%
“…CXCL8 was found elevated in DM and CADM associated with anti-MDA5 or anti-ARS Ab compared to HD in one study [62]. CXCL8 seems to be implicated in CADM and ILD since serum level was increased in CADM compared to that in classical DM with ILD and HD [52] and in RP-ILD but not in C-ILD compared to non-ILD [65] or in ILD compared to non-ILD in anti-MDA5 or anti-ARS-Ab-positive patients [62]; however, in this last study, in multiple linear regression analysis CXCL8 was not associated with ILD. A positive correlation was found between CXCL8 and MITAX [62], global VAS, pulmonary VAS, and serum ferritin level [65].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we did not evaluate changes to other inflammatory cytokines, including serum interleukin (IL)-6, IL-8, IL-10, IL-18, interferon (IFN)-α, IFN-γ, macrophage colony-stimulating factor, CX3CL1, or messenger RNA levels of CD11b in circulating neutrophils, which have also been indicated to represent pathogenic factors for RPIP. [20][21][22][23][24][25] Activation of monocytes and macrophages through these factors has been suggested to underlie the pathophysiology of anti-MDA5 Ab-positive DM patients. 20,25 Further studies should be conducted to elucidate whether removal of these factors with TPE contributes to disease control.…”
Section: Discussionmentioning
confidence: 99%